(untitled) (LEARNing Landscapes, 2007)
In this article the various dimensions of student engagement are examined. Based on understandings derived from her doctoral research, the author shows how engagement is realized through various levels of participation identified as assigned participation, shared participation and participative tone. She demonstrates that to enhance any theoretical explanation of engagement, one must include or "invite in" those being observed. The voices of students enrich the dialogue about how to define engagement. More importantly, the students articulate what needs to be done to make learning meaningful for them.